Penerapan Metode Geolistrik Untuk Identifikasi Pola Penyebaran Zona Asin Di Bledug Kuwu, Grobogan, Jawa Tengah - Darman D; Cari C; Darsono D (Department of Physics, Sebelas Maret University, 2016)
Geoelectrical is one of geophysics methods which is used to investigate the early stage in the shallow exploration. The research is conducted at Bledug Kuwu with Schlumberger configuration method containing the two points of potential electrodes and the two points of electrical current electrodes. The equipment used in this research are OYO model 2119C, GPS, meter roll, cable as current and potential electrodes. The purpose of the research is to identify the spreading pattern of salty zone at Bledug Kuwu. The distribution pattern of salty zone is characterized by thickness of 1.55 to 71.9 meters and rangeresistivity of 0.055 to 0.460 Ωm. At west of large Bledug, the salty zone is detected at the depth of 5.0 to 10.0 meters and 30.0 to 50.0 meters. Meanwhile at east of large Bledug, the salty zone is detected at the depth of 5.0 to 15.0 meters and 40.0 to 60.0 meters. The salty zone spread from north to south at both west and east of large Bledug with resistivity of 0.05 to 0.50 Ωm at depth of 5.0 to 50.0 meters.